Reject water characterization and treatment through short‐cut nitrification/denitrification: assessing the effect of temperature and type of substrate. Issue 12 (13th July 2018) - Noutsopoulos, Constantinos; Mamais, Daniel; Statiris, Evangelos; Lerias, Eleftherios; Malamis, Simos; Andreadakis, Andreas
Abstract: BACKGROUND: The objectives of this study were to provide a detailed qualitative and quantitative characterization of different reject water types and to evaluate the effect of temperature and type of external organic carbon source on short‐cut nitrification/denitrification process performance for the treatment of reject water with a high ammonia content. RESULTS: According to the results reject water originating from the sludge dewatering unit is characterized by a high ammonium‐nitrogen content which can be further increased upon pre‐treating the sludge in a thermal‐hydrolysis unit, a low carbon to nitrogen ratio, a low biodegradability and contributes approximately 75% of the total ammonium‐nitrogen load of the recycled flows. It is anticipated that the process can be sustained even at low temperatures (15°C). The temperature effect on both nitritation/denitritation rates is described by an Arrhenius equation with activation energies equal to 37.6 and 39.6 kJ mol −1 respectively. The addition of an organic carbon source rich in easily biodegradable compounds can provide for the achievement of high denitritation rates (in the order of 10 mgNO2 ‐N gVSS‐1 h −1 ). CONCLUSION: An interesting low cost option to reserve on‐site an easily biodegradable organic carbon source by integrating different processes in a wastewater treatment plant is primary sludge hydrolysis. © 2018 Society of Chemical Industry